(untitled) (OODBODHAN, 2026)
Growing urbanization has led to the extensive transformation of Land Use and Land Cover (LULC) within irrigation command areas, altering land-use patterns and increasing pressure on water resources. In Nepal, changes in command areas have not been objectively recorded. The objective of this study was to evaluate historical trends and provide simulations and predictions for land use land cover change (LULCC), focusing specifically on cropland and built-up areas within the Phewa Irrigation System Command Area (PIS-CA). Landsat 7 satellite imagery for the years 2002 and 2012 and Sentinel-2 satellite imagery for 2022 and 2025 were analyzed within ArcGIS software, utilizing pixel-based supervised image classification. The study predicts urban expansion for the years 2032 and 2042 using the CA-Markov model and Land Change Modeler (LCM). Model validity was assessed by comparing actual 2022 LULC with predicted results. Input variables included topography, distance to major roads, distance to the urban core of Pokhara, and proximity to rivers and lakes. The results showed that between 2002 and 2022, cropland decreased by 152.94 hectares (51.31%) at an average annual rate of 2.56%, while the built-up area increased by 149.84 hectares (400.18%) at a rate of 20.05% per year. From 2022 to 2042, the area under cropland is projected to decrease by 57.54 hectares (39.36%) at a rate of 1.96% per year, while the built-up area is expected to increase by 69.53 hectares (35.36%) at a rate of 1.76% per year. Based on the cropland area on the classified LULC map of 2025 and the present cropping pattern in the command area of the Phewa irrigation system, the irrigation water requirement during the peak period is 1296.66 lps. Further, the predicted irrigation water requirements for the years 2032 and 2042 are 993.96 lps and 906.22 lps, respectively.